La métaphore de l'arbre nouvel outil d'orientation pour la clientèle féminine - Spain, Armelle; Hamel, Sylvie (Canadian Journal of Counselling and Psychotherapy, 1993)
In this article, the authors present the tree as a metaphor for exploring, understanding and intervening within a career counselling process with women. The specificity of women's personal development, particularly of their vocational development as previous research by our team has shown, constitute the theoretical bases for this new counselling tool. The tree as a metaphor is described through its components, through its complexes and through its own inherent movement. A glimpse of the program tided Devenir, built on this metaphor and originally conceived and finalized by the authors, is given. Finally the use of the tree questions both the theoretical premises and the practice of career counselling for women.